A formação do professor em diferentes espaços socializadores: um olhar sobre os alunos do curso Pedagogia da Terra da UFRN - Costa, Gilberto Ferreira (2006)
﻿This work is an analysis about the teacher's formation starting from certain aspects of its culture. It is supposed that the teacher is constituted in an individual that acts starting from singular aspects, in an individual point of view, but at the same time it interacts with other individuals in an environment strongly marked by the culture. Those two dimensions are representatives of the socio-cultural characteristics and they can be seen in the perspective of the individual and collective identity. Based on those presuppositions we chose, as reference, four environment of formation: the family, the school, the work and the Movement of the Rural Workers Without-Soil/MST (MST: The without-soil-ones in Portuguese) observing as the teachers refers to those environment highlighting, mostly, the formative aspects stood out. The individuals researched are teachers involved in the education of settled communities, who are students of the Earth Pedagogy course of the Universidade Federal do Rio Grande do Norte/UFFRN. For our analyses, we used narrative texts, written by the teachers, as conclusion of the discipline History of the Brazilian Education in which they tell their life histories. The speeches show as the environments of reference influence in their world conceptions, attitudes and values that not just mix in an individual dimension, but also collective. The research make us reflect about the possibility to think on the educational action starting from that understanding of wide formation considering the present elements in the courses of teacher's life